Effect of Propolis bees on some pathogenic microbes of humans - Khadija Abdulla Abu Annizah , Younes Abu Bakr Al–Khayali (Journal of Pure & Applied Sciences, 2018)
Propolis is one of the natural products collected by bees from different plants, which was used by the old man to treat many diseases, and the current study investigated the activity against a sample of Libyan Propolis against a number of pathogenic microbes are as follows: (Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, Bacillus Cereus, and Salmonella choleraesuis, Proteus vulgaris And, Candida albicans) The results showed that the extract of the propolis had the antimicrobial effect under study. The results showed that the effect varied according to the extract and the microbe. The increase in the concentration of the extract was accompanied by an increase in inhibiting microbial growth. The concentrations of 75% -100% were better for their killer and the pesticide. 50%, there was weak growth and there was heavy growth at concentrations ranging between 5% -25%. , And a comparison was made between the effectiveness of these extracts and antibiotics commonly used.